Prevalence of Hyperacusis in the General and Special Populations: A Scoping Review - Ren, Jing; Xu, Tao; Xiang, Tao; Pu, Jun-mei; Liu, Lu; Xiao, Yan; Lai, Dan (Frontiers in Neurology, 2021)
Objectives: To study the prevalence of hyperacusis in the general population and the special population, and to determine the effect of population differences on hyperacusis. Methods: The two authors followed a scoping review methodology and screened nearly 30 years of English literature in Pubmed, Web of Science, OVID, and EBSCO. Then, the extracted results of each study were discussed in groups and subgroups. Results: The authors selected 42 pieces of scientific literature that met the requirements, studying a total of 34,796 subjects, including the general population (28,425 subjects), the special occupation population (2,746 subjects), and the patients with concomitant diseases (5,093 subjects). The prevalence was 0.2%–17.2% in the general population, 3.8%–67% in the special occupation population, and 4.7%–95% in the patients with special diseases. It was found that in the general population, the highest prevalence occurs in adolescents and older adults. The prevalence of hyperacusis in women is significantly higher than in men. In people with hearing disorders, the prevalence of hyperacusis is significantly higher than in people with normal hearing. Various diseases (such as Williams syndrome, tinnitus, and autism), as well as various occupations (musicians, music students, teachers, and others), have been found to be high risk factors for hyperacusis. Conclusion: The high prevalence of hyperacusis and the large differences between reported prevalence in different studies deserves our great attention. Additionally, in order to increase the comparability of the studies, a standardized set of criteria are needed to study the prevalence of hyperacusis.